PENGARUH MODEL SUGESTI-IMAJINASI TERHADAP KETERAMPILAN MENULIS ANEKDOT - Dina Dwi Syafitri; Abdoel Gafar; firman Tara (Universitas Batanghari, 2018)
This research is aimed at identifying the use of suggestion-imagination model towards anecdote writing. This research is quantitative. The design of this research is pretest and posttest group. The population of this research is class X MIPA 3 students of SMA Negeri 10 Kota Jambi. The sampel is taken by using purposive sampling. Test is used in collecting the data. There are two tests are used, they are; pretest and posttest. The data are analyzed by using normality test, and homogeneity test is used to find the result of hypothesis. The research result shows that the mean of posttest is 67,18 and pretest is 58,59. The hypothesis test is used for t-test in which tcount is 7,857 and ttable is 2,353. It means that this result is equivalent with the criterion in which Ho is rejected and Ha is accepted. So it can be concluded that suggestion-imagination model has significant influence towards students of class X MIPA 3 in writing anecdote inSMA Negeri 10 Kota Jambi Academic Year 2016/2017. Hence, the suggestion-imagination model can be used in learning anecdote writing.Key Words : suggestion-imagination, writing, anecdote.